Sensor interface for body pressure monitoring device - Pu, Junran (2017)
Most people with diabetes suffer from diabetic foot ulcers and requires amputation if the condition becomes serious. Foot pressure measurement devices can help patients monitor their foot pressure at any time, sending alert to patients when their foot pressure is high. This allows patients to change their behavior to reduce the foot pressure. There are many foot pressure measurement devices, however, the device size of the existing product is large. In this project, a sensor interface system is designed to measure the foot pressure. This sensor interface system consists mainly of a multi-channel Wheatstone bridge, operational amplifier, analog-to-digital converter, multiplexer and voltage regulator. The multi-channel Wheatstone bridge is used to measure the resistance change of the sensors through the measure of the output voltage change of the bridge. The operational amplifier is used to amplify the output voltage of the multi-channel Wheatstone bridge to meet the voltage requirement of the analog-to-digital converter (ADC). The FPGA from digital part determines which sensors are connected to the circuit by controlling the multiplexer. A voltage regulator can supply a stable power to avoid voltage fluctuation using a supply voltage of 3.3V, thus, the power consumption of the sensor interface system is reduced. A PCB has been fabricated to verify the design. The size and performance of this sensor interface system are optimized. Through the PCB testing, the relationship between the sensor resistance and output voltage of the operational amplifier is obtained. The testing results verify that the sensor interface system developed can accurately measure the resistance change of the sensor. Besides, this sensor interface system is connected to the FPGA to control the multiplexer for acquisition of data.